Impressive : printmaking, letterpress and graphic design - Klanten, Robert; Hellige, Hendrik (Berlin : Gestalten, 2010)
Today's graphic designers, illustrators, and typographers are rediscovering old printing techniques and handcrafts.The work collected in this book shows the many facets of the graphic design business, from business cards to posters.
Editors from colophon.
Includes index.
Keywords: Graphic design (Typography).; Prints -- Technique; Letterpress printing; Graphic arts